RIS Development and Implementation in a mm-waves 5G NR System Towards 6G - Silva, Luiz Gustavo (2023)
This work presents the conception and development of a novel 1024-element reconfigurable intelligent surface (RIS), using split-ring resonator (SRR) based 2-bit unit cells and tuned by varactor diodes in the millimeter waves (mm-waves) frequency band at 24.5 GHz with 400 MHz bandwidth. The RIS printed unit cell has been conceived using the full-wave electromagnetic solver ANSYS HFSS, comprising four layers based on two different substrates from Rogers, namely: 0.508-mm thick RO3003 and 0.1-mm thick bonding RO4450. The entire unit cell element encompasses four conducting layers, in which the first two ones form the SRR, whereas RF chokes are printed at the middle layer to isolate the DC circuit and the bias lines are routed at the fourth layer, resulting in a 0.245x0.245 ?? 2 total area. The 2-bit unit cell measured resonance frequency ranges from 22.4 to 25.52 GHz, resulting in a phase shifting greater than 270?? at 24.5 GHz. The proposed 2-bit RIS design uses the finite array domain decomposition method (FADDM) and radar cross-section (RCS) approachesin ANSYS HFSS. Beam steering generation from -60?? to 60?? in the azimuth plane is achieved by the 1024 elements arranged in a 32x32 matrix with a linear gradient phase controlled columnwise. The proposed RIS is characterized by reflection pattern performance under different incident wave angle conditions and beam steering angles. Reflection patterns from 30?? to 60?? are experimentally demonstrated with a scan loss of 4.1 dB. Additionally, a low-power consumption RIS control board is proposed and fabricated using a standard microcontroller, single-pole four-throw (SP4T) switches, digital-to-analog converters (DAC) and I/O expanders, resulting in an average power consumption of only 331 mW. Using the same transversal dimensions for the RIS and control board gives rise to a compact solution with 103x120x14 mm3 total area. Finally, a demonstrator is presented using the proposed mm-waves RIS in an indoor environment using a real 5G New Radio (NR) signal and following the 3 rd Generation Partnership Project (3GPP) Release 18 performance requirements. Such experiment uses a 64-quadrature amplitude modulation (QAM) 5G-NR signal at 24.5 GHz with a bandwidth of up to 400 MHz, achieving a maximum throughput of 1.2 Gbps. The RIS deployment results in a channel power and signal-to-noise ratio (SNR) improvement of 21.5 and 23.8 dB, respectively.